IoT-Driven Innovations in Psychosocial Care for Breast Cancer Survivors - A Review - Owolabi, Wuraola Foluke; Ogunkorede, Olufunke Agatha; Akpor, Oluwaseyi Abiodun; Afolalu, Adeniran Sunday (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
Internet of Things (IoT) technologies are developing at a rapid pace, which could greatly improve the psychosocial support provided to breast cancer survivors. The intersection of Internet of Things (IoT) technologies and psychosocial care represents a transformative avenue for improving the quality of life of breast cancer survivors. This review explores recent advancements in IoT applications in psychosocial care, focusing on their role in addressing emotional, psychological, and social challenges faced by survivors. The discussion encompasses IoT-enabled wearable devices, mobile health applications, and smart environments that facilitate remote monitoring, real-time interventions, and personalized support. Challenges and future research directions are also examined to guide stakeholders in leveraging IoT innovations for holistic care. This also explores the integration of IoT innovations in addressing the unique psychosocial challenges faced by these individuals. By examining existing literature and case studies, we identify key areas where IoT can facilitate improved mental health support, enhance communication between patients and healthcare providers, and promote a sense of community among survivors. The findings suggest that IoT-driven solutions can lead to better health outcomes and quality of life for breast cancer survivors.